2009
DOI: 10.1016/j.ijgo.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dysplasia in Nigerian women infected with HIV

Abstract: A high prevalence of cervical dysplasia was found among HIV-positive Nigerian women, which was associated with increased immune suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 22 publications
7
53
6
Order By: Relevance
“…The prevalence of 28.2% as found in this study is high but comparable to 27% reported in UK by Hotonu et al (2010) and 31.3% in Maiduguri, Northern Nigeria by Chama et al (2005). It is however lower than 68.3 and 43.7% prevalence rates reported in Jos, Nigeria by Agaba et al (2009) and in Kenya by Mabeya et al (2012). A lower rate of 12.6% was reported in Enugu by Dim et al (2011).…”
Section: Discussionsupporting
confidence: 60%
“…The prevalence of 28.2% as found in this study is high but comparable to 27% reported in UK by Hotonu et al (2010) and 31.3% in Maiduguri, Northern Nigeria by Chama et al (2005). It is however lower than 68.3 and 43.7% prevalence rates reported in Jos, Nigeria by Agaba et al (2009) and in Kenya by Mabeya et al (2012). A lower rate of 12.6% was reported in Enugu by Dim et al (2011).…”
Section: Discussionsupporting
confidence: 60%
“…In countries where women have poor access to medical care, rates of CIN2/3 or more severe lesions could be higher. 18 HIV-infected women have a higher prevalence of HPV infection overall and high-risk HPV infection in particular. 19 We found an overall HPV prevalence of 69.2% among 494 HIV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…HPV detection by PCR was carried out in a nested-PCR system, using the primers MY09/11 and GP5+/6+. DNA was amplified with specific primers for HPV types 6,11,16,18,31,33 and 35, in independent reactions. Sequencing reaction of nested-PCR product was used when HPV types were not identified by the former primers.…”
Section: Introductionmentioning
confidence: 99%
“…This was comparable to a study conducted in Cameroun which reported a prevalence of 43.5% [20], further giving credence to the fact that CIN changes are more in patients with HIV infection. Other studies conducted in Nigeria and Ethiopia, however, showed lower prevalence rates [21,22]. The difference in the prevalence rates may be due to the use of cytological smears for the diagnosis of CIN as opposed to histologically confirmed lesions used in this study.…”
Section: Discussionmentioning
confidence: 58%